Spy School secret service : a spy school novel - Gibbs, Stuart, 1969- (New York : Simon & Schuster Books for Young Readers, 2017)
Thirteen-year-old Ben Ripley is assigned to protect the president from an assassination attempt in his first solo mission, but he may be in over his head
Sequel to: Spy ski school
008-012
Accelerated Reader AR
Step 6
Keywords: Assassination -- Juvenile fiction; Presidents -- Juvenile fiction; Friendship -- Juvenile fiction; Schools -- Juvenile fiction; Spies -- Fiction; Assassination -- Fiction; Presidents -- Fiction; Friendship -- Fiction; Schools -- Fiction; Washington (D.C.) -- Juvenile fiction; Washington (D.C.) -- Fiction; Children's stories; Spy stories; Humorous stories; Spy fiction